FIB-4 Regression With Direct-Acting Antiviral Therapy in Patients With Hepatitis C Infection: A Safety-Net Hospital Experience - Ghoneim, Sara; Butt, Muhammad Umer; Trujillo, Sophie; Asaad, Imad (Frontiers in Medicine, 2020)
Background: Liver fibrosis stage determines the risk of morbidity and mortality from chronic hepatitis C virus (HCV) infection. The majority of HCV-infected patients are underserved and have other comorbid conditions that lead to more progressive liver disease such as cirrhosis and hepatocellular carcinoma. Safety net hospitals are the prime location to treat these patients. Direct acting antiviral (DAA) agents are highly effective in virus eradication. Aim: We aimed to evaluate the effect of treatment with DAAs on FIB-4 index. Methods: We identified 343 patients who initiated HCV treatment with DAAs from 2016 to 2018 and achieved a sustained virologic response (SVR) in Metrohealth Medical Center, a safety net hospital system. We compared the severity of hepatic fibrosis before and one year after SVR was attained. We evaluated whether the presence of other comorbid conditions influenced liver fibrosis regression. All analyses were performed using SAS software. Results: There was a statistically significant drop in mean FIB-4 score from baseline to post-SVR (3.47± 2.84 vs 2.28 ± 1.60, P <0.001). 117 patients had baseline FIB-4 scores > 3.25, 56% had FIB-4 scores <3.25 after SVR. Alcohol use disorder was associated with a higher baseline FIB-4 score compared to low level drinking (3.85± 0.20 vs.3.15± 0.16). These patients showed greater improvement in FIB-4 scores after treatment when compared to those without alcohol use disorder (1.44+0.15 vs. 0.97±0.13, P =0.02). Conclusion FIB-4 index is a useful non-invasive tool for monitoring fibrosis regression after antiviral therapy. Patients with a history of alcohol abuse had the greatest reduction in FIB-4 score post-SVR.